Isolation and Characterization of Plant Growth Promoting Bacteria from Seleniferous Soil - Chadha, Akansha (My University, 2018)
Due to the increased human activities and a number of natural conditions, the environment is getting contaminated. One such factor is the formation of the seleniferous soil which plays a vital role in the contamination of an ecosystem. Patches of seleniferous soil have been found in north-eastern parts of Punjab. The underground water of this region is highly rich in seleniferous materials as it gets transported from Siwalik hills through small rivulets. Not only humans, the livestock and plants are also affected by the increased concentration of selenium. There are a number of microorganisms which are not only able to tolerate its high concentration but also promote the growth of the plants in that soil by releasing various metabolites. The objective of the present work was to isolate the selenium-tolerant bacteria and to determine its role in plant growth promotion by using selenium-contaminated soil. The present work also demonstrates the amount of selenium accumulated by the isolated bacteria as well as in plant tissues which were treated with it. In the present study, two Se-tolerant bacteria were isolated and were further screened for plant growth promotion. The two strains, B49 and B71 identified as Leclercia adecarboxylata and Cedecea neteri respectively have been able to tolerate upto 300 mM of sodium selenite and show IAA production, phosphate solubilization and ammonia production. They were able to produce 46.89 and 69.91µg /ml of IAA respectively. The phosphate solubilization index shown by them is 1.26 and 1.39 respectively. These isolates have also been found to transform one form of selenium into another. Two months nursery trials were also conducted to check selenium tolerance and plant growth promotion in vivo. A remarkable increase in the plant height, root length, shoot length, shoot biomass and root biomass as compared to control plants with no inoculum were observed. Therefore, these bacterial strains can be potentially used in the soils contaminated with selenium for plant growth promotion and bioaccumulation of selenium by plants for increased tolerance and further practices such as biofortification of food grains.
Keywords: Selenium, seleniferous region, Cedecea neteri, Leclercia adecarboxylata, bioaccumulation